ANALISIS SOSIOLOGI OLAHRAGA TERHADAP PENGARUH POLITIK DAN MEDIA SOSIAL DI KALANGAN MASYARAKAT: STUDI PUSTAKA - Manurung, Sarah Yemimah; Manurung, Dani Ela; Surbakti, Jepri; Sibarani, Arnold Andriano; Laurens, Martin; Lumbanraja, Wanri; Surbakti, Ibrena Syahputra; Simamora, Dedi Parinton; Hutaruk, Calvin Laser; Peranginangin, Jonas Noel; Siregar, Yan Indra; Arima, Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of politics and social media from the perspective of sports sociology in society. In the modern era, sports are not only understood as physical activities and entertainment but also as social phenomena closely related to power, media, culture, and the development of digital technology. This research used a qualitative method with a literature study approach by collecting data from national journals, books, and various relevant scientific literatures. The data analysis technique was carried out using descriptive qualitative analysis and content analysis to understand the relationship between sports, politics, and social media in community life. The results showed that politics has a significant influence on the world of sports, especially in image building, nationalism, and power interests. Meanwhile, social media plays an important role in disseminating sports information, shaping public opinion, and increasing public participation in sports activities. In addition to providing positive impacts such as increasing interest in sports and forming social communities, social media also creates negative impacts in the form of excessive fanaticism, the spread of hoaxes, and social conflicts among sports supporters. Therefore, society needs to have awareness in using social media wisely so that sports can remain a positive medium in social life.